Analysis of rain cell size distribution from meteorological radar data for rain attenuation studies - Khamis, Nor Hisham (2005)
The ability of radar to scan a wide area around the radar site and not just a particular path made it a very attractive for many types of investigations. Radar can be used to measure the rainfall rate indirectly. This is achieved by knowing the radar reflectivity and then converting them into rainfall rate. The S-band frequency of the meteorological radar ensures that propagation effects such as attenuation are negligible. Radar provides valuable information that is relevant in modelling rain-induced propagation effects. Radar also provides spatially and temporally continuous measurements that are immediately available at one location. Rain cell size distribution is obtained from radar data. 'Virtual' microwave links of 20-km path lengths were constructed in the scanning area of the radar. However, rain cell size distribution from radar data is limited to 1-km integration size. This is due to the fact that the radar uses a range bin size of 1 km. The radar data is obtained from the Kluang Radar Station of the Meteorological Department of Malaysia. This paper present an analysis of rain cell size distribution obtained from the meteorological radar data. Rain cell size is an important parameter in the study of attenuation of radio propagation through rain. This parameter is used for attenuation predictions, link budget estimation, microwave system planning, slant path rain attenuation modeling and remote sensing of the Earth's surface, and have important applications in attenuation mitigation techniques such as space diversity. Analysis was done to find the rain cell size distribution.